2021
DOI: 10.1111/jtsb.12310
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and investigating relationality in the capability approach

Abstract: The capability approach (CA) is a framework for understanding, assessing, and promoting the quality of human lives and social justice. It focuses on capabilities – people's freedoms and opportunities to live in valuable ways. Although its proponents readily acknowledge that capabilities can depend on personal, social and environmental factors, little attention has been paid to the ontology of capabilities (what they are and how they are caused and constituted) and the inherent relationality of the approach is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Such approaches underscore the need to understand agency as mediated by political and cultural structures of power associated with capitalism, gender inequality and the legacies of colonialism, respectively. As Owens et al (2022) make clear, the relational dimensions of the CA also make it potentially compatible with complex systems theory, itself a key perspective for understanding the environmental crisis, its causes and its potential remedies. 2 From this relational perspective, the discussion below examines some of the important personal, material and social conversion factors which affect the agency of HE educators and shape their capabilities to teach the crisis.…”
Section: Understanding Educator's Capabilities To Teach the Crisis: I...mentioning
confidence: 99%
“…Such approaches underscore the need to understand agency as mediated by political and cultural structures of power associated with capitalism, gender inequality and the legacies of colonialism, respectively. As Owens et al (2022) make clear, the relational dimensions of the CA also make it potentially compatible with complex systems theory, itself a key perspective for understanding the environmental crisis, its causes and its potential remedies. 2 From this relational perspective, the discussion below examines some of the important personal, material and social conversion factors which affect the agency of HE educators and shape their capabilities to teach the crisis.…”
Section: Understanding Educator's Capabilities To Teach the Crisis: I...mentioning
confidence: 99%
“…As an example [137], studied assistive technologies using the HCA and the biopsychosocial model of disability. On the other hand [138], deployed a HCA within a critical realist philosophy to study mobile phone use among people with disabilities [139], showed the possibility of blending critical realism, hermeneutics, and complexity theory to develop a relational ontology of capabilities.…”
Section: Generic Implicationsmentioning
confidence: 99%
“…The concept of person-centredness is variously explained and interpreted but includes notions of health professionals focusing on the person not just the disease, working respectfully with the person, enabling their agency, orienting to address the person’s own concerns and priorities for their wellbeing, and recognising the practical realities of their lives [ 5 , 10 ]. The latter may be particularly important when poverty and social inequality constrain people’s scope to improve their health via lifestyle ‘choices’ [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%